PRINSIP TANGGUNGJAWAB KOMANDAN DALAM PERSPEKTIF HUKUM PIDANA ISLAM (JINAYAH) - Ria Wulandari (Al-Maslahah : Jurnal Ilmu Syariah, 2017)
Abstract Article 28 (a.1) of the Rome Statute of the International Criminal Court 1998 states that the commander shall be criminally responsible for crime if it meets the element of knowing or should know that his troops were commiting or about to commit a crime. This is different for civilian officials or superiors who are only criminally responsible for crime if the superiors either knew, or consciously disregarded information which clearly indicated, that the sobrodinates were commiting or about to commit such crimes (article 28 (b.1). These two rule differences (for commanders and civil officials) are believed to be article 28 has weakened the power of dolus and culpa elements or even ignorance of subordinate crimes. It is necessary to see the provisions of the commander's responsibility from the perspective of Islamic criminal law which may differ from both the element and punishment. This paper highlighted the genocide crime. Genocide means any of the following acts committed with intent to destroy, in whole or in part, a national, ethnical, racial or religious groups (article 6 of the Rome Statute of 1998). The Islamic criminal law does not govern the genocide but has regulated punishment for the person who ordered the criminal acts (murder) as well as punishment for acts committed intentionally or unintentionally. From the existing principles of Islamic criminal law can be drawn a legal argument about punishment for the commander in which his forces committed a genocida crime.Keywords: Responsibility of Commander, Islam Criminal Law (Jinayah). Abstrak Pasal 28 (a.1) Statuta Roma 1998 menyebutkan bahwa komandan bertanggungjawab secara pidana jika memenuhi unsur mengetahui atau seharusnya mengetahui bahwa pasukannya melakukan suatu tindak pidana. Hal ini berbeda untuk pejabat sipil atau atasan dimana yang dikenakan tanggungjawab pidana hanya yang mengetahui atau secara sadar tidak menghiraukan informasi bawahan yang melakukan tindak pidana (pasal 28 (b.1). Dari kedua perbedaan aturan (untuk komandan dan pejabat sipil) diyakini pasal 28 telah melemahkan kekuatan elemen dolus (kesengajaan) dan culpa (kelalaian) atau bahkan tidak mengetahui sama sekali kejahatan bawahan. Perlu kiranya melihat ketentuan mengenai pertanggungjawaban komandan dari perspektif hukum pidana Islam yang kemungkinan memiliki perbedaan baik dari unsur maupun penghukumannya. Penghukuman tindak pidana yang disorot dalam tulisan ini adalah genocida. Genocida adalah perbuatan yang dilakukan dengan maksud untuk menghancurkan atau memusnahkan seluruh atau sebagian kelompok bangsa, ras, kelompok etnis, kelompok agama(pasal 6 Statuta Roma tahun 1998). Hukum Pidana Islam tidak mengatur mengenai genocida namun telah mengatur hukuman bagi orang yang menyuruh melakukan perbuatan pidana (pembunuhan) serta hukuman bagi perbuatan yang dilakukan dengan sengaja atau tidak sengaja. Dari asas-asas Hukum Pidana Islam yang telah ada dapat ditarik suatu argument hukum tentang hukuman bagi komandan yang mana pasukannya melakukan tindak pidana genocida.Kata Kunci: Tanggungjawab Komandan, Hukum Pidana Islam (Jinayah), Genocida.